The Application of Rubber Ball Grip Therapy to Improve Muscle Strength in Non-Hemorrhagic Stroke Patients in the Stroke Unit of RSD Gunung Jati Cirebon - Purbaningsih, Endah Sari; Akhbar, Juliansyah (INDOGENIUS, 2025)
Background & Objective: According to the World Health Organization (WHO), stroke is a clinical syndrome characterized by brain dysfunction symptoms, which may result in death or lasting disability if symptoms persist beyond twenty-four hours. It can cause physical disabilities, loss of function, paralysis, and communication difficulties. This study aimed to analyze nursing care interventions using Rubber Ball Grip Therapy in non-hemorrhagic stroke patients to improve muscle strength. Method: The study employed a case study design with one non-hemorrhagic stroke patient experiencing muscle weakness at RSD Gunung Jati Cirebon. Data collection was conducted through anamnesis, physical assessment, direct observation, and documentation. Nursing care was provided for 3 consecutive days. At admission, the patient complained of weakness in the right extremities and numbness since the previous evening, accompanied by headaches. The intervention used was Mobilization Support with evidence-based nursing (EBN) Rubber Ball Grip Therapy, implemented for 15 minutes daily over 3 consecutive days. Result: The therapy was found effective as the patient, initially weak, was later able to grip the rubber ball firmly. Conclusion: Rubber Ball Grip Therapy was effective in improving muscle strength in a non-hemorrhagic stroke patient. This simple, non-pharmacological intervention can support motor recovery and be applied in nursing care practice.